ACCESS AND UTILIZATION OF INPUTS FOR MAIZE PRODUCTION: EVIDENCE FROM OBAFEMI OWODE LOCAL GOVERNMENT AREA, OGUN STATE, NIGERIA - Koledoye, G. F.; Kenneth, A. I.; Arogunrerin, R. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigates types, sources, levels, and intensity of input use among maize farmers in Obafemi Owode Local Government Area (LGA), Ogun State. A cross-sectional survey was conducted with 107 randomly selected farmers across four maize-producing communities. Data were collected using structured questionnaires and analyzed with descriptive statistics and the Input Utilization Index (IUI). Findings reveal that farmers predominantly rely on herbicides (99.1%), crude implements (96.3%), inorganic fertilizers (73.8%), and improved seeds (61.7%), while long-term productivity-enhancing inputs such as mechanization (38.3%), irrigation (22.4%), and storage facilities (25.2%) are underutilized. Input acquisition is dominated by personal savings and agro-shops, whereas institutional sources like ADP, research institutes, and NGOs play marginal roles. The IUI distribution shows a near balance between lower–moderate (50.5%) and higher (49.5%) users, with no significant gender differences (p = 0.599). These results underscore the systemic constraints of credit access, land tenure insecurity, and weak institutional support, which limit sustainable input use. Strengthening cooperatives, embedding extension services within agro-dealer networks, and revitalizing institutional delivery channels are critical to enhancing maize productivity and farmer welfare in Southwestern Nigeria.